2020
DOI: 10.1007/s00391-020-01779-2
|View full text |Cite
|
Sign up to set email alerts
|

How do dementia researchers view support tools for informed consent procedures of persons with dementia?

Abstract: The study aimed to assess how dementia researchers view eight support tools that have been defined to enhance informed consent (IC) procedures for people with dementia (PwD). In an online survey, 19 dementia researchers from Germany and Portugal evaluated the tools in terms of 4 implementation criteria. Overall, they all had a very positive attitude towards the support tools, whereby the tools person-centered attitude of the researcher and elaborated plain language were the most highly rated of the eight tools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…In addition, one could use supported decision-making strategies that facilitate the understanding and retrieval of verbal information, such as the presentation of information in short, thematically grouped segments in plain language, augmented by written summaries. For more information on strategies for supported decision-making, see Wied et al (2019), Wied, Haberstroh, et al (2021), and Wied, Poth, et al (2021). This requires of the medical personnel a resource-oriented attitude toward PwD as well as the readiness for ongoing training on the topic of the capacity to consent and resource-oriented communication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one could use supported decision-making strategies that facilitate the understanding and retrieval of verbal information, such as the presentation of information in short, thematically grouped segments in plain language, augmented by written summaries. For more information on strategies for supported decision-making, see Wied et al (2019), Wied, Haberstroh, et al (2021), and Wied, Poth, et al (2021). This requires of the medical personnel a resource-oriented attitude toward PwD as well as the readiness for ongoing training on the topic of the capacity to consent and resource-oriented communication.…”
Section: Discussionmentioning
confidence: 99%
“…This evaluation was based on problem-centered interviews with every ECP participant. An additional small study was conducted, to investigate dementia researchers view on the developed tools ( 25 ). In brief, we performed an online survey with 19 dementia researchers from Germany and Portugal and evaluated the tools in terms of 4 implementation criteria.…”
Section: Discussionmentioning
confidence: 99%
“…A study that addressed whether PWD can give informed consent to participate in research reported that they could decide through the simplified decision-making process of choosing between options. These methods reduced their difficulty in understanding and interpreting by complementing their cognitive functions and enabling decision-making on their part [61], thereby supporting their autonomy. Ultimately, maintaining the autonomy of PWD leads to the preservation of their sense of personhood.…”
Section: Discussionmentioning
confidence: 99%